GAMBARAN MASYARAKAT INGGRIS DALAM PRIDE AND PREJUDICE: SUATU ANALISIS SOSIOLOGI SASTRA - LOINDONG, PAMELA CLARA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
Literature and society are like two sides of a coin, they cannot be separated. Through literature, we could see how the author depicts the society and their social circumstances. Literature is a representation of life. It reflects the life itself, or, in other words, it is life, which literature imitates or mirrors; and we can say that the subject matter of literature is the manifold experiences of human beings and society (Wellek and Warren 1949:89). Pride and Prejudice is one of Jane Austen’s masterpieces. It is a story about relationship, life and love. Jane Austen is very popular with her intelligent and meticulous in describing the detail about British community’s social life, especially in the early nineteenth century. How eminently Jane Austen creates a masterpiece such as Pride and Prejudice — which simultaneously makes it a portrait and a wonderful portrayal of the life of the early opportunists’ society in the early nineteenth century — is something that is very interesting to be explored. The objectives of this research are: (1) to identify, analyze and describe how Jane Austen’s Pride and Prejudice depicts the social life and circumstances of British society in the early nineteenth century; and (2) to identify, analyze and describe how is the social stratification depicted in Jane Austen’s Pride and Prejudice. To analyze this novel, the writer uses sociological approach, mimetic theory from Aristotle, the theory of relation between sociology and literature from Wellek and Warren, and social stratification theory from Max Weber. Pride and Prejudice intelligently and realistically depicts the British social life in the early nineteenth century. The depictions are through correspondence as medium of communication and ballroom dance party as medium of socialization. Furthermore, through theme of the story, Austen also depicts the awful social reality at that time on how society assumes marriage as the highest aspiration a woman could achieve, value of marriage and the requirement about what values should a woman held. Social stratification in British society is also depicted in Pride and Prejudice. Social stratification theory by Max Weber states that status, class and power are required and must be fulfilled to attain a certain position in social dimension. Through some characters in Pride and Prejudice, we could see the implementation of this theory. Keywords: pride and prejudice, sociological approach, social stratification, theory of relation